Modelling transmission and control of Toxoplasma gondii in New Zealand farmland - Rachelle N. Binny; Graham J. Hickling; Alex James; Chris N. Niebuhr (Royal Society Open Science)
Toxoplasma gondii is one of the world’s most prevalent parasites and has significant impacts on the health of humans, domestic animals and wildlife. In New Zealand’s rural environments, T. gondii creates economic losses for the farming industry and threatens vulnerable native avifauna and marine mammals. Predator control of rodents and feral cats has potential to reduce or even eliminate transmission of T. gondii on farms; however, the efficacy of such management is uncertain. We apply a mathematical model of T. gondii transmission dynamics in feral cat and rodent populations in New Zealand farmland and simulate varying intensities of predator control to predict changes in T. gondii prevalence and environmental contamination levels over time. The model predicts that predator control is relatively ineffective for reducing transmission in areas with high environmental contamination rates. However, assuming low rates of environmental contamination, local elimination of T. gondii could be achievable, for example, by control that sustains large reductions of 88%, 69% and 59% in feral cat, house mouse and ship rat populations, respectively, over 56 weeks. Predator control is, therefore, a potentially viable approach for managing T. gondii in some rural environments, but only if high levels of population control are sustained.